Temporal evolution of carbon footprint and emission reduction pathways of major crops in Inner mongolia under China’s dual-carbon goals - Jiuwei Chi; Na Liu; Fang Wang; Jingran Yu; Xiao Zhang; Chuang Yue; Rifu Bada (PLoS ONE, 2026)
As an important grain-producing region in northern China, the Inner Mongolia Autonomous Region is characterized by arid and semi-arid agricultural ecosystems, limited water resources, and relatively high dependence on agricultural inputs such as irrigation, chemical fertilizers, diesel fuel, and plastic film mulching. Clarifying the temporal evolution of input-related carbon footprints in crop production is important for promoting agricultural low-carbon transformation while maintaining regional food security. Based on an input-based carbon footprint accounting framework with reference to life cycle assessment principles, this study quantified the carbon footprint of major crop production in Inner Mongolia from 2006 to 2023. Six major emission sources were considered: chemical fertilizers, pesticides, agricultural plastic film, diesel fuel, irrigation, and soil tillage. The results showed that agricultural input use experienced a transition from rapid expansion to partial stabilization. Fertilizer, pesticide, and diesel consumption increased during the early and middle stages of the study period and then stabilized or declined after the mid-2010s, whereas plastic film use continued to increase.The reported effective irrigated area increased sharply in 2022. This increase should be interpreted primarily as a statistical breakpoint caused by the official application of the Third National Land Survey results and the updated land-use classification system, rather than as a sudden one-year physical expansion of irrigation. The total carbon footprint increased from 448.88 × 10⁴ t CO₂-eq in 2006 to 720.07 × 10⁴ t CO₂-eq in 2023, representing an increase of 60.4%. Cropland tillage and chemical fertilizer application were the dominant emission sources, accounting for 38.2%–45.9% and 25.1%–31.4% of total emissions, respectively. Although the total carbon footprint and carbon footprint per unit planted area increased, the carbon footprint per unit agricultural output value decreased by 66.8%, indicating improved carbon-economic efficiency. However, this decline may also be influenced by market price changes and crop value structure. The findings suggest that future mitigation should focus on conservation tillage, precise fertilizer management, water-saving and energy-efficient irrigation, plastic film recycling or substitution, and improved agricultural carbon monitoring. This study provides a regional-scale reference for developing low-carbon agricultural pathways in arid and semi-arid farming systems.